Effects of Grape Pomace on Sow Blood, Colostrum and Milk Parameters - Michal Rolinec; Eva Mixtajová; Branislav Gálik; Ondrej Hanušovský; Milan Šimko; Zuzana Schubertová; Anton Kováčik; Renata Vargová; Viera Madajová; Miroslav Juráček (Agriculture)
This study was performed to assess the effects of grape pomace feeding on the immunoglobulin concentration in mammary gland secretions and the biochemical parameters of sows’ blood. This study presents unique results of sow blood parameters obtained during the first day postpartum. Sixteen gestating sows were included in the experiment. The experimental group (DGP) received a supplement of dried grape pomace in the amount of 1% of the basal diet from the 7th day antepartum until the end of lactation. Blood, colostrum, and milk were taken from the sows. On the 1st day postpartum, in the sows’ blood, higher values of total proteins and globulins, as well as lower values of aspartate aminotransferase, creatinine, and the albumin/globulin ratio, were recorded in DGP. There were no significant differences in the concentration of immunoglobulins in the blood of sows between the groups. Also, differences in the concentrations of immunoglobulins in the colostrum and milk of sows throughout lactation were not statistically significant. It can be stated that the feeding of dried grape pomace did not have a negative effect on the biochemical parameters of the sows’ blood, colostrum, and milk. In addition, there is a potential suggestion that the addition of dried grape pomace could have a positive effect on the antioxidant status of sows.